When Media Violence Awakens our Better Nature: The Effect of Unpleasant Violence on Reactivity toward and Enjoyment of Media Violence. Issue 4 (2nd October 2019) - Waddell, T. Franklin; Bailey, Erica; Weber, Marcela; Ivory, James D.; Downs, Edward
Abstract : The effects of violent media on aggression-related outcomes is an ongoing debate, often focusing on the effects of violence portrayals that are sanitized for the viewer. However, narratives that focus on the real world consequences of violence are also known to receive critical acclaim and broad exposure. Do unpleasant portrayals of violence affect viewers' subsequent reactivity to violence? Results from two laboratory studies show that priorexposure to unpleasant violence increases donation behavior to assist victims of real world violence (N = 60) and decreases enjoyment of fictional media violence (N = 109). The implications of these findings are discussed.